Transition from androgenic to neurosteroidal action of 5α-androstane-3α, 17β-diol through the type A γ-aminobutyric acid receptor in prostate cancer progression. Issue 178 (April 2018) - Xia, Ding; Lai, Doan V.; Wu, Weijuan; Webb, Zachary D.; Yang, Qing; Zhao, Lichao; Yu, Zhongxin; Thorpe, Jessica E.; Disch, Bryan C.; Ihnat, Michael A.; Jayaraman, Muralidharan; Dhanasekaran, Danny N.; et al.
Graphical abstract: Highlights: AKR1C3 and GABAA R were co-expressed in radical prostatectomy specimens. 3α-diol promoted PCa cells growth in vitro and in ovo . 3α-diol-stimulated proliferative and molecular effects can act through GABAA R. 3α-diol-activated EGFR-Src pathway can be placed downstream of from the GABAA R. Abstract: Androgen ablation is the standard of care prescribed to patients with advanced or metastatic prostate cancer (PCa) to slow down disease progression. Unfortunately, a majority of PCa patients under androgen ablation progress to castration-resistant prostate cancer (CRPC). Several mechanisms including alternative intra-prostatic androgen production and androgen-independent androgen receptor (AR) activation have been proposed for CRPC progression. Aldo-keto reductase family 1 member C3 (AKR1C3), a multi-functional steroid metabolizing enzyme, is specifically expressed in the cytoplasm of PCa cells; and positive immunoreactivity of the type A γ-aminobutyric acid receptor (GABAA R), an ionotropic receptor and ligand-gated ion channel, is detected on the membrane of PCa cells. We studied a total of 72 radical prostatectomy cases by immunohistochemistry, and identified that 21 cases exhibited positive immunoreactivities for both AKR1C3 and GABAA R. In the dual positive cancer cases, AKR1C3 and GABAA R subunit α1 were either expressed in the same cells or in neighboring cells. Among several possible substrates, AKR1C3 reduces 5α-dihydrotesterone (DHT) to form 5α-androstane-3α, 17β-diol (3α-diol). 3α-diol is a neurosteroid that acts as a positive allosteric modulator of the GABAA R in the central nervous system (CNS). We examined the hypothesis that 3α-diol-regulated pathological effects in the prostate are GABAA R-dependent, but are independent of the AR. In GABAA R-positive, AR-negative human PCa PC-3 cells, 3α-diol significantly stimulated cell growth in culture and the in ovo chorioallantoic membrane (CAM) xenograft model. 3α-diol also up-regulated expression of the epidermal growth factor (EGF) family of growth factors and activation of EGF receptor (EGFR) and Src as measured by quantitative polymerase chain reaction and immunoblotting, respectively. Inclusion of GABAA R antagonists reversed 3α-diol-stimulated tumor cell growth, expression of EGF family members, and activation of EGFR and Src to the level observed in untreated cells. Results from the present study suggest that 3α-diol may act as an alternative intra-prostatic neurosteroid that activates AR-independent PCa progression. The involvement of AKR1C3-mediated steroid metabolisms in modulating GABAA R activation and promoting PCa progression requires continued studies.